2003
DOI: 10.1002/anie.200352100
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of an Amine Oxidase Possessing both Broad Substrate Specificity and High Enantioselectivity

Abstract: Enantiomerically pure chiral amines are of increasing value in organic synthesis, especially as resolving agents, [1] chiral auxiliaries/chiral bases, [2] and catalysts for asymmetric synthesis. [3] In addition, chiral amines often possess pronounced biological activity in their own right and hence are in demand as intermediates for agrochemicals and pharmaceuticals. [4] Current methods for the preparation of enantiomerically pure chiral amines are largely based upon the resolution of racemates, either by recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(96 citation statements)
references
References 27 publications
2
93
0
1
Order By: Relevance
“…Hence, we tried to coax the enzyme to accept L-sialic acid by expanding the scope of its substrate specificity with an analogue, L-KDO, which is easier to synthesize (11). Although enzyme adaptation for substrate analogues is unpredictable (19), it has been demonstrated that activities of some substrate analogues do increase throughout the course of directed evolution (10,14,20). The wild-type sialic acid aldolase exhibits a low level of activity toward D-and L-KDO (5,21).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we tried to coax the enzyme to accept L-sialic acid by expanding the scope of its substrate specificity with an analogue, L-KDO, which is easier to synthesize (11). Although enzyme adaptation for substrate analogues is unpredictable (19), it has been demonstrated that activities of some substrate analogues do increase throughout the course of directed evolution (10,14,20). The wild-type sialic acid aldolase exhibits a low level of activity toward D-and L-KDO (5,21).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we believe that enzymecatalyzed enantioselective partial oxidations will become more important in the future, especially when synthetic catalysts fail completely (65). Preliminary studies in our laboratories concerning the directed evolution of a cyclohexanone monooxygenase as a biocatalyst in the Baeyer-Villiger reaction of 4-hydroxycyclohexanone show that the enantioselectivity of this synthetically interesting transformation can be increased substantially from ee ϭ 9% to ee ϭ 90%.…”
Section: Directed Evolution Of Other Enzymesmentioning
confidence: 99%
“…Examples of each of these are described in Figure 10. [224][225][226] Improved enantioselectivity, catalytic activity at increased substrate concentration Example C: 227 Inversion of enantioselectivity Example D: 228 …”
Section: Practical Applications Of Genetically Modified Enzymesmentioning
confidence: 99%